PENGARUH CORPORATE GOVERNANCE, ARUS KAS BEBAS DAN LEVERAGE TERHADAP MANAJEMEN LABA - Romarion Utama Siregar; Paulus Th Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2019)
This study aims to analyze and provide empirical evidence of the influence of the implementation of corporate governance mechanisms on earnings management at manufacturing companies listed on the Indonesia Stock Exchange. The independent variables used are corporate governance represented by institutional ownership, board of directors, board of independent comissioners, supported by free cash flow, firm size, and leverage while the dependent variable used is earnings management. The populations in this study are manufacturing companies listed on the Indonesia Stock Exchange in the period 2014-2016. The sample of this study consists of 318 companies listed in Indonesia Stock Exchange. The data that was used in this study was secondary data and sample selection using purposive sampling method. The analysis model uses multiple linear regression analysis. Based on the results of the analysis shows that the variable of institutional ownership has a positive effect on earnings management, but the hypothesis is rejected because contrary to hypothesis of this study which institutional ownership negatively affect earnings management. Variable free cash flow have significant influence toward earnings management, while variable board of directors, board of independent comissioners, firm size and leverage have no significant effect on earnings management.